MicroRNA-203a-3p as a Modulator of Doxorubicin Resistance in Hepatocellular Carcinoma: Molecular and Metabolic Insights - Abdelaal, Noha Mohamed (AUC Knowledge Fountain, 2026)
Hepatocellular carcinoma (HCC) continues to be a significant global health concern, ranking third in mortality rates among all cancer types. Despite therapeutic advancements, doxorubicin (DOX) remains a cornerstone chemotherapeutic agent in the treatment of HCC. However, its efficacy is often limited by the development of drug resistance. Increased cellular capacity to repair DNA damage is a key molecular mechanism underlying DOX resistance. MicroRNAs (miRNAs) are a family of small, non-protein-coding RNA molecules that regulate gene expression post-transcriptionally. They have emerged as critical regulators of tumorigenesis and are considered promising biomarkers and therapeutic targets. Among them, miR-203a-3p has been implicated in modulating chemoresistance in various cancer types, though its role in HCC remains unclear. In this study, we employed a comprehensive approach to investigate the functional role of miR-203a-3p in response to DOX treatment in HCC. To elucidate the underlying mechanisms, we combined cytotoxicity assays, gene expression analysis, apoptosis assays, and metabolic profiling, using HepG2 and Huh7 cells, which differ in p53 status. Our findings offer new insights into the role of miR-203a-3p in the context of HCC chemoresistance, with potential implications for therapeutic interventions. Understanding the molecular and metabolic underpinnings of miR-203a3p function may inform the development of more effective miRNA-based combination therapies to overcome chemoresistance and improve treatment outcomes.